The influence of glutathion S-transferase P-1 polymorphism A313G rs1695 on the susceptibility to cyclophosphamide hematologic toxicity in Indonesian patients (Faculty of Medicine Universitas Indonesia, 2016)
Background: Chemotherapy often causes side effects such as hematologic toxicity. The degree of toxicity is often associated with genetic polymorphism. This study aims to determine the influence of GSTP1 A313G polymorphism, an enzyme responsible for detoxifying cyclophosphamid, on incidence and severity of cyclophosphamid hematologic toxicity. Methods: 91 Indonesian females diagnosed with breast cancer at Haji Adam Malik Central General Hospital, Medan, receiving cyclophosphamide, doxorubicin/epirubicin and 5-FU were included in this retrospective cohort study. DNA was extracted from peripheral leukocytes and GSTP1 A313G genotyping was analyzed using polymerase chain reaction-restriction length fragment polymorphism (PCR-RFLP). Genotype deviation and allele frequencies were also determined by Hardy-Weinberg Equilibrium. The degrees of hematologic toxicity (leucopenia and neutropenia data after chemotherapy cycles 1 and 3) were collected from the patient medical records. The data were analyzed using chi-square test. Results: 60.4% of the patients had the wildtype (A/A), while 29.7% were heterozygous (A/G), and 9.9% were homozygous mutant (G/G). There was no significant deviation of allele and genotype frequency from Hardy-Weinberg Equilibrium. The G allele (A/G & G/G) contributes to more severe degree of leukopenia compared to patients with wild type allele (A/A) (p<0.05) after the 3rd chemotherapy cycles. Conclusion: There was association between GSTP1 polymorphism with the degree of hematologic toxicity in breast cancer patients receiving cyclophosphamide chemotherapy regimen.